Chilean educational centers and the external counselling process: A look from the perspective of its protagonists - Garay Aguilar, Mario Fabian; Sánchez Moreno, Marita (Education Policy Analysis Archives, 2017)
The article presents the analysis of the assessment and perception of school principals, teachers and advisors with regard to the counselling processes developed in the context of the Preferential School Subsidy Law (PSS Law) developed in Punta Arenas (Chile). The purpose of this law is to help teachers to introduce future improvements in the teaching practice carried out in the classroom, and with that, to increase the students’ learning in the standardized tests. The investigation was focused on the analysis of the counselling process for the progress from the perspective of the actors involved in the process: counsellors, teachers and school principals in 17 public primary schools in Punta Arenas. A mixed quantitative-qualitative method was applied.  A questionnaire ad hoc was designed and in-depth interviews were conducted. The results confirm that it is unrealistic to expect that the current counselling and accountability policies for results guarantee a quality education with equity if the Preferential School Subsidy Law (PSS Law) is not strengthened.  By doing so, more autonomy would be given to the schools for selecting consultancy according to their needs and demanding the minimum standards for quality to the consultant companies. Therefore, the present research work intends to translate the findings obtained and grant them as inputs that allow the school leaders to make wiser decisions in matters of educational counselling.